Cognitive restructuring as a panacea for maladaptive behaviors among primary school children - Bisong, Nonso Ngozika; Ntamu, Blessing Agbo; Undelikwo, Veronica Akwenabuaye (International Journal of Evaluation and Research in Education (IJERE), 2025)
This study investigated the efficacy of cognitive restructuring as a panacea for maladaptive behaviors among primary school children in Calabar Municipal, Cross River State, Nigeria. The study was a quasi-experimental study using a pre-test-post-test experimental design. Data were collected from pupils in primary four. Data was collected over twelve weeks. The mean and standard deviation of the pre-and post-test scores were calculated and analysis of covariance (ANCOVA) was used to determine the differences in the two scores. There were 39 students recruited for the study. The study found that maladaptive behaviors such as aggression and disobedience were pervasive among primary school pupils in Calabar. Notably, the findings indicated that cognitive restructuring had a statistically significant impact on reducing aggressive behavior, though its influence on disobedient behavior was not as pronounced. The paper concluded that cognitive restructuring is an effective intervention strategy for addressing maladaptive behaviors among primary school pupils. The intervention achieved its intended goal of improving children’s behavior and provided a framework for more sustainable behavior management strategies.